Pattern of referral and management of oro-dental problems in patients with cancer: a retrospective study - Das, Kaberi; Krishnatreya, Manigreeva; Kataki, Amal Chandra (International Journal of Research in Medical Sciences, 2017)
Background: General dentistry care is of paramount importance in maintaining oral hygiene of cancer patients. Methods: The data of patients registered at the dental wing in a tertiary care cancer center for one year period (2013) was used for the present analysis. All the cases were retrospectively analyzed for the pattern of referral, diagnosis of different oro-dental conditions, and different interventions done for the various oro-dental conditions. Results: A total of 798 patients were referred from various oncology wings for management of oro-dental problems, 50.1% patients were referred from head and neck oncology, 31% were from radiation department, 6.2% patients were from medical oncology and palliative care department each, 4% patients were from gynecologic oncology, and 2.5% patients were from screening wing. Acute gingivitis (62%) in pre treatment and mucositis (28%) in post treatment were major symptoms and signs for referral. 47% patients were managed with tooth extraction, grinding was done on 23%, scaling were done on 12.5%, desensitization was done on 8.7% patients, filling was done on 2.5% patients, prosthesis fitting in 2.5% patients, root canal treatment in 2.2% patients, and post surgical obturator fittings in 0.75% patients. Conclusion: Majority of cancer patients were referred for oro-dental care from head and neck oncology department with head and neck cancers and extraction of tooth pre radiotherapy and chemotherapy remains an important part of oro-dental care in cancer patients.